Epidemiological Study of Betacoronaviruses in Captive Malayan Pangolins - Li, Linmiao; Wang, Xiaohu; Hua, Yan; Liu, Ping; Zhou, Jiabin; Chen, Jing; An, Fuyu; Hou, Fanghui; Huang, Wenzhong; Chen, Jinping (Frontiers in Microbiology, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) has tremendously affected international public health safety. It has been reported that the pathogen severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes COVID-19, could originate from bats and utilize the Malayan pangolin (Manis javanica) as an intermediate host. To gain further insights into the coronaviruses carried by pangolins, we investigated the occurrence of Betacoronaviruses (β-CoVs) infections in captive Malayan pangolins in the Guangdong province of China. We detected three β-CoVs-positive M. javanica individuals with a positive rate of 6.98% and we also detected β-CoVs in two dead pangolins sampled in August 2019. The CoV carried by pangolins is a new β-CoV, which is genetically related to SARS-CoV-2 and can live in pangolins for a long period. Moreover, sequence analysis based on the N gene of β-CoVs showed that there were mutations at the nucleic and amino acid levels among pangolins. Furthermore, the expression of angiotensin-converting enzyme 2 (ACE2) were detected in eight organs of pangolins with the highest ACE2 mRNA levels in the kidney, suggesting that these organs could be at a risk of β-CoVs infection. On comparing ACE2 with 17 amino acids at the main binding site of the S protein of SARS-CoV and SARS-CoV-2, it was found that pangolins were more susceptible to infection with these pathogens. Furthermore, the pangolin-CoV had the ability for cross-species spread. These results enable us to better understand the status of β-CoVs carried by Malayan pangolins, while providing a theoretical basis for better pangolin protection and viral control.